2019
DOI: 10.1001/jamaoncol.2019.1011
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Safety of Glucocorticoid Regimens in Combination With Abiraterone Acetate for Metastatic Castration-Resistant Prostate Cancer

Abstract: Key Points Question What are the physiological effects associated with abiraterone acetate plus various glucocorticoid regimens to treat metastatic castration-resistant prostate cancer? Findings In this open-label, phase 2 randomized clinical trial, the 164 men with metastatic castration-resistant prostate cancer treated with abiraterone acetate plus prednisone, 5 mg, twice or once daily, 2.5 mg twice daily, or dexamethasone, 0.5 mg, once daily showed no mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Previous studies demonstrate relationships between ARSi therapy and lipid metabolism and statin use (23)(24)(25). Both abiraterone and enzalutamide can induce increases in body fat mass and decreases in lean body mass (26,27). However, the relationship between body composition and the response to ARSi in CRPC patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate relationships between ARSi therapy and lipid metabolism and statin use (23)(24)(25). Both abiraterone and enzalutamide can induce increases in body fat mass and decreases in lean body mass (26,27). However, the relationship between body composition and the response to ARSi in CRPC patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no glucocorticoid-related side effects were reported in postdocetaxel patients with mCRPC. However, limited patients were included in Atarrd et al [19] and our studies. Therefore, further studies are required to evaluate the possible side effects induced by oral glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…This lower dosage of prednisolone has been cited as a reason for the relatively high proportion of mineralcorticoid-related adverse events, including fluid retention, hypertension and hypokalaemia, among participants in the LATITUDE trial. The co-administration of different glucorticoid regimens with abiraterone acetate in patients with mCRPC has been explored in a prospective clinical trial, with the results suggesting there is little scope for reducing prednisolone doses while still preventing mineralcorticoid excess [48].…”
Section: Concomitant Steroid Administrationmentioning
confidence: 99%